A trend towards increasing viral load in newly diagnosed HIV-infected inpatients in southeast China. Issue 8 (6th January 2016) - CHEN, Y.; WANG, Z.; HUANG, A.; YUAN, J.; WEI, D.; YE, H.
SUMMARY: Peripheral blood viral load is an important indicator of viral production and clearance. Previous studies have suggested that viral load might predict the rate of decrease in CD4 + cell count and progression to AIDS and death. Here, we conducted a retrospective analysis of the trends in HIV-1 viral load in southeast China. Among inpatients newly diagnosed with HIV infection, we found that viral load has increased over the past decade from 4·20 log10 copies/ml in 2002 to 6·61 log10 copies/ml in 2014, with a mean increase of 0·19 log10 copies/ml each year. However, the CD4 + cell count was stable and insensitive to changes in viral load. Thus, increasing viral load appears to be an emerging trend in newly diagnosed HIV-infected inpatients.